Funeral traditions of Romans and barbarians of Gallia in I-III centuries AD - Khrul Anastasiia (Studia Humanitatis, 2023)
Death and funeral traditions in the pre-Christian era have been studied in different degree, thoroughly in the cultures of ancient Rome and ancient Greece, much less in detail in the cultures of pagans, who in Europe were commonly called barbarians. The article is an attempt to comparatively analyze the customs and rituals of burial of the dead in the Roman Empire and Gallia in the I-III centuries AD. The paper shows the main similarities and differences of funeral traditions in these cultures and their mutual influence.